Gaya Kepemimpinan, Tunjangan Kinerja Dan Motivasi Kerja Pengaruhnya Terhadap Kinerja Pegawai Sekretariat Daerah Kota Batu (Studi Bagian Protokol Dan Komunikasi Pimpinan) - Afita Puji Chrismawati; Hadi Sunaryo; Nanik Wahyuningtyas (UNIVERSITAS ISLAM MALANG, 2023)
Abstract The purpose of this study was to determine the effect of leadership style, performance allowances, and work motivation on employee performance in the Protocol and Communication Section of the Regional Secretariat of Batu City.By using a sample of 48 people. Data analysis methods used in this research are descriptive statistics and inferential statistics.This study also indicates that the results of the study show that simultaneously the variables of leadership style, performance allowances, and work motivation have a positive and significant effect on employee performance in the Protocol and Communication Section of the Regional Secretariat of Batu City.Based on the results of partial testing (t test) the leadership style variable has a positive and significant effect on employee performance, the performance allowance variable has a positive and significant effect on employee performance and the work motivation variable has a positive and significant effect on employee performance in the Protocol and Communication Section of the Regional Secretariat of Batu City. Keywords: Leadership Style, Performance Benefits, and Work Motivation and Employee Performance